Predictive Maintenance by Electrical Signature Analysis to Induction Motors - Bonaldi, Erik Leandro; Oliveira, Levy Ely de Lacerda de; Silva, Jonas Guedes Borges da; Lambert-Torresm, Germano; Silva, Luiz Eduardo Borges da (IntechOpen, 2012)
None